Save Nature to Survive N 13(2): 281-283, 2018 (Supplement on Agronomy) www.thebioscan.com 281 INFLUENCE OF INTEGRATED NUTRIENT MANAGEMENT ON GROWTH, YIELD AND FRUIT QUALITY OF APPLE CV. RED DELICIOUS DELICIOUS - RATURI, VIPIN; THAKUR, NIDHIKA; MANJU NEGI (The Bioscan, 2018)
Apple is main table fruit of temperate region. It is rich in minerals, vitamins and antioxidants, those protect from several disease. An investigation was therefore undertaken to increase the production and quality of apple with suitable nutrient management. The experiment was laid out in various combinations of inorganic fertilizers (urea, SSP and MOP), FYM and vermicompost. Among all the treatments, treatment T4 [60% inorganic fertilizers + 40% organic matter (vermicompost)] performed best where highest annual shoot growth (64.07 cm), tree height increment (0.55 cm), tree volume (23.54 m3), fruit yield (72.40 kg/ tree), fruit weight (229.42 g), fruit length (8.39 cm), fruit breadth (8.14 cm), fruit volume (290.89 cm3), total soluble solids (13.04 ºB), reducing sugars (5.76 %), non reducing sugars (4.10 %) and total sugars (10.08 %) were observed. Present investigation revealed that the combination of organic manures along with inorganic fertilizers was found effective in improving the yield, fruit quality and soil health of apple orchard.